2022
DOI: 10.3748/wjg.v28.i30.4019
|View full text |Cite
|
Sign up to set email alerts
|

Role of one-step nucleic acid amplification in colorectal cancer lymph node metastases detection

Abstract: Current histopathological staging procedures in colorectal cancer (CRC) depend on midline division of the lymph nodes (LNs) with one section of hematoxylin and eosin staining. Cancer cells outside this transection line may be missed, which could lead to understaging of Union for International Cancer Control Stage II high-risk patients. The one-step nucleic acid amplification (OSNA) assay has emerged as a rapid molecular diagnostic tool for LN metastases detection. It is a molecular technique that can analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 207 publications
(225 reference statements)
0
6
0
Order By: Relevance
“…We had 1.1% false negatives, but this rate has been reported up to 15.4% in other series [61]. Despite this limitation, almost all published studies have shown good performance of this technique, showing a high sensitivity (90.4%), specificity (96.8%), concordance (96.0%), positive predictive value (79.8%), and negative predictive value (98.6%) [28,65]. In this regard, OSNA LN staging can be improved and achieve its full clinical significance and impact in early-stage CRC only through a complete analysis of the LN tissue.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…We had 1.1% false negatives, but this rate has been reported up to 15.4% in other series [61]. Despite this limitation, almost all published studies have shown good performance of this technique, showing a high sensitivity (90.4%), specificity (96.8%), concordance (96.0%), positive predictive value (79.8%), and negative predictive value (98.6%) [28,65]. In this regard, OSNA LN staging can be improved and achieve its full clinical significance and impact in early-stage CRC only through a complete analysis of the LN tissue.…”
Section: Discussionmentioning
confidence: 58%
“…This could be solved by submitting the whole LN for molecular analysis, as carried out in LNs from breast carcinoma [13,28]. In fact, all the OSNA studies on CRC to date have used similar methodologies, with part of the LN used for H&E and part used for OSNA, which may be the reason for the false negativities and the limiting of its applicability in general practice [65]. We had 1.1% false negatives, but this rate has been reported up to 15.4% in other series [61].…”
Section: Discussionmentioning
confidence: 99%
“…These studies pave the way for a new molecular staging using OSNA based on the amount of CK19mRNA rather than the number of LN metastases. Furthermore, TTL has been suggested to be related to a poor prognosis, worse disease-free survival, and other CRC risk factors[ 45 , 93 , 94 ], such as pN, pT, tumor grade, male sex, tumor size, and lymph vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Individual imaging modalities face specific intrinsic limitations, which negatively impact detection and it does not allow a correct evaluation of important lymph node (LN) details. Therefore we only have the size criterion available to determine lymphadenopathies[ 45 ]. A new semi-automated diagnostic method called one-step nucleic acid amplification (OSNA) has been developed to detect LN metastases.…”
Section: Introductionmentioning
confidence: 99%
“…This nonexposed approach prevents possible peritoneal spillage and at the same time allows for full-thickness resection. Compared with laparoscopic wedge resection, NEWS enables minimal tissue resection, especially in difficult positions [4]. Early data on NEWS and sentinel node mapping have demonstrated their safety and efficacy [4,5].…”
Section: Endoscopic Submucosal Dissection (Esd)mentioning
confidence: 99%